The Contribution of IQ (Intelligence Quotient), Anxiety, and Concentration to the Achievement of Central Java Chess Athletes - Hanfin, Zahra Chumaira Amelia; Setyawati, Heny; Kusuma, Donny Wira Yudha (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2022)
Chess is required to think extra and to have the foresight to master the game, to read the opponent's characteristics and walk smartly. Chess athletes can't get enough from their intelligence levels and low anxiety, but they have to counter with good concentration. The purpose of this study is to provide information and input for the development of chess games to identify IQ levels (intelligence quotient), anxiety levels and concentration levels of athletes and to analyze the psychological aspects of chess players during a game. The research approach with mixed method is that of correlated and ethnography qualitative. Instruments used in questionnaire, interview guidelines and documentation. The population and samples of the semarang city's chess player number 20 athletes made up of 12 men and 8 girls. Statistical hypothesis test carried out using version 23 of SPSS software. Research shows the value of sig IQ (intelligence quotient) 0.020.05 with assigned variable IQ (intelligence quotient) by 22.3 percent. On sig 's anxiety indicates a value of 0.033.05 with variable anxiety contributions of 32.8%. At the concentration of the sig shows a value of 0.007 < 0.05 with variable contribution of 44.3%. Sig indicates a value of 0.041 0.05, which indicates an IQ contribution (intelligence quotient), anxiety and concentration of central javan chess player with a variable IQ contribution (intelligence quotient), anxiety and concentration of 59.5%.